2017
DOI: 10.1111/aji.12653
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, placental ageing‐related pathologies and adverse pregnancy outcomes

Abstract: Oxidative stress (OS), an imbalance between free radical generation and antioxidant defence, is recognized as a key factor in the pathogenesis of adverse pregnancy outcomes. Although OS is a common future of normal pregnancy, persistent, overwhelming OS leads to consumption and decline of antioxidants, affecting placental antioxidant capacity and reducing systems. The accumulation of OS causes damage to lipids, proteins and DNA in the placental tissue that induces a form of accelerated ageing.Premature ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
196
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(201 citation statements)
references
References 113 publications
4
196
0
1
Order By: Relevance
“…The increase in RNA and this enzyme implies the possibility of a significant rise in its product, NO. 53,54 Our findings indicate that T. cruzi Oxidative stress is associated with placental hypoxia, the imbalance of cytokines, impairment of trophoblast invasion and implantation, which result in poor fetal development but with pathologies different to Chagas. 13,37 This phenomenon led us to postulate that NO may have been reacting with ROS and forming peroxynitrites.…”
Section: Congenital Transmission Has Been Reported In Different Countmentioning
confidence: 79%
“…The increase in RNA and this enzyme implies the possibility of a significant rise in its product, NO. 53,54 Our findings indicate that T. cruzi Oxidative stress is associated with placental hypoxia, the imbalance of cytokines, impairment of trophoblast invasion and implantation, which result in poor fetal development but with pathologies different to Chagas. 13,37 This phenomenon led us to postulate that NO may have been reacting with ROS and forming peroxynitrites.…”
Section: Congenital Transmission Has Been Reported In Different Countmentioning
confidence: 79%
“…Furthermore, it is well established that saturated fats such as PA are associated with the adverse effects of HFD consumption and obesity. 25 Although OS is a common feature of normal pregnancy, persistent, overwhelming OS leads to the consumption and decline of antioxidants, affecting placental antioxidant capacity and reducing systems. [20][21][22] However, to our knowledge, our study is the first to in- Oxidative stress can be defined as an imbalance between free radical generation and antioxidant defense and is recognized as a key factor in the pathogenesis of adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…19. Previous studies have shown that PA induces cytotoxicity in a diverse set of cells including trophoblasts, skeletal muscle, and liver cells. 25 Indeed, the accumulation of OS causes damage to lipids, 25 Although OS is a common feature of normal pregnancy, persistent, overwhelming OS leads to the consumption and decline of antioxidants, affecting placental antioxidant capacity and reducing systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a common feature of normal pregnancy, but persistent, overwhelming OS leads to consumption and decline of antioxidants, affecting placental antioxidant capacity with subsequent damage of placental tissue components (9) ; thus inducing a form of accelerated placental ageing (10) . In addition, ROS could stimulate platelet adhesion and aggregation leading to intravascular coagulopathy with subsequent placental infarction and impairment of the uteroplacental blood flow (11) .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%